GUT BRAIN AXIS IN AUTISM SPECTRUM DISORDERS - AYURVEDIC PERSPECTIVE - Anirudhan, *Roshni; Shajahan, M A (International Journal of Ayurveda and Pharma Research, 2019)
Autism spectrum disorder (ASD) constitutes a group of brain developmental disorders, and it is defined by stereotyped behaviour and deficits in communication and social interaction. The prevalence of ASD has shown an alarming increase in the recent decades ending up to 1 in 90 children. The exact cause of ASD is still not known. Research studies have focused on genetic causes, dysregulation of the immune system, inflammation, exposure to environmental toxicants, and the defective gut microbiota. Accumulating evidence demonstrates that gastrointestinal symptoms, such as abdominal pain, gaseousness, diarrhea, constipation and flatulence, are a common comorbidity in patients with ASD. The gut consists of millions of microbiota, and we hypothesize that the microbiota and its metabolites might be involved in the pathophysiology of ASD. In Ayurveda all Psycho social abnormalities have been included under the category of Unmada. A defective digestive and metabolic function is postulated as the root cause of Unmada, leading to systemic accumulation of metabolic wastes (Dhatugataama). The metabolic wastes act as systemic toxins and impair the functional integrity of brain. An observational study was carried out in the outpatient section of the Department of Kaumarabhrithya, Govt. Ayurveda College Hospital for Women and Children, Poojappura, Thiruvananthapuram in 122 children with ASD. Data pertaining to Socio demographic aspects and clinical manifestations were recorded and its prevalence rate was calculated. It was noted that 54% of the cases showed an evident disturbance in the digestive mechanism. Constipation was complained by 28% of cases, bloated abdomen by 16%, irritable bowel by 8%, increased flatulence by 7% and recurrent diarrhoea by 3%. Although these studies did not show a cause-effect relationship between GI symptoms and ASD, the findings suggest that the gut plays an important role in the etiology of ASD. Ayurvedic treatment strategies that modulate the gut microbiota might constitute a potential therapy for patients with ASD.